The Determination of Visual Inspection in Women of Childbearing Age - Fatwa Imelda; Mula Tarigan; Lidya Eryunika (Talenta Publisher, 2021)
Cervical cancer is the most common disease affecting women around the world. Early detection of cervical cancer is needed by using Visual Inspection with Acetic Acid (VIA). This method is relatively easy to do, and the examination costs are also quite affordable, making it more beneficial for women. This study was to determine the determinants of the VIA Test results. It is quantitative research with a descriptive approach presented in the form of a frequency distribution table. There are 100 samples of women of childbearing age acquired by purposive sampling at Patumbak District, Deli Serdang. From the samples, some respondents receive positive IVA test result as follows: 14% aged 36-35 years old, 14% Protestant, 19% married, 9% high school graduates, 10% housewife, 15% with minimum monthly income, 12% with 3-5 children, 17% has multigravida parity, 14% married at the age of 17-25 years old, 12% first-time mother at the age of 17-25 years old, and 14% with 5+ years using IUD contraception. The study was based on the negative VIA test result but with detected pre-cancerous lesions. Further research with different variables is necessary to acquire more information regarding cervicitis incidence causes, thus, reducing cervical cancer numbers.